A child with airway obstruction secondary to tracheal abnormality with associated pulmonary artery sling - Chan, Yee Jean; Abd. Aziz, Azian; S, Hasri; Abdullah, Ahmad Fadzil (2009)
Tracheal obstruction can be due to tracheal stenosis or tracheal anomaly rather than from compression by pulmonary artery sling when both are present in a patient. Patient can present with signs and symptoms of airway obstruction without swallowing problems. We present a case of this rare condition.